Ontogenetic characteristics of anxiety of gymnasts of high sports qualification - Milashechkina, E. A.; Gernet, I. N.; Timofeeva, O. V.; Buchnev, S. S.; Pogorelova, O. V.; Milashechkin, V. S. (International Journal of Applied Exercise Physiology, 2019)
Aim: We have identified age-related changes in the level of anxiety in athletes involved in rhythmic gymnastics. In this article the need for a differentiated approach of psychological preparation is proved, when planning a training process in different periods of ontogenesis of gymnasts. In the rhythmic gymnastics it is a necessity to make a decision on the preparation of a training course.